(untitled) (Research, Society and Development, 2023)
Given the magnitude of diabetes mellitus in the Brazilian context, which includes a rapid process of demographic transitions, epidemiological transition with a triple burden of diseases, together with recent cuts in investments in public health, it is crucial to reflect on the adequacy of care for diabetic elderly people and its implications. Therefore, the objective of the present study is to carry out a literature review that highlights the importance of the pharmaceutical professional in guiding and monitoring diabetic elderly people, focusing on drugstores. A narrative bibliographic review research was conducted, descriptive and exploratory in nature. Pharmaceutical care plays a vital role in promoting health, especially in the elderly, where polypharmacy is prevalent. The literature review highlights the importance of the pharmacist in identifying and preventing Medication-Related Problems (DRP), focusing on medication adherence and the management of chronic conditions, such as diabetes. The strategic presence of pharmacists in a large number of establishments in Brazil reinforces their accessibility. Future research could explore the integration of technologies to optimize pharmaceutical care in older adults, targeting personalized strategies that improve adherence and reduce DRP, promoting an innovative, patient-centered approach to optimizing treatment outcomes and quality of life.